Artifacts in MRI: Villain or Hero? Using Artifacts for Diagnosing Central Nervous System Diseases - Morais, Gabriela Lopes de; Peruzini, Gilmar Filho; Rosa-Júnior, Marcos (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2021)
An artifact is a feature present in an image which is not part of the original structure. It can occur as a consequence of several factors. It may be mistaken for pathologic conditions, leading to adverse consequences for the patients. The aim of the present study is to present a selection of the main artifacts described in brain and spinal magnetic resonance images to improve the ability of the physicians to recognize them and to reduce their interference on the final interpretation of a scan. The authors searched the scientific community for artifacts in magnetic resonance imaging (MRI), which were selected to focus on central nervous system (CNS) findings. With the Picture Archiving and Communication System (PACS) database from the center where this study was conducted, the authors designated brain and spine MRI scans with conspicuous artifacts to compose the present study. The artifacts were then classified as those that contribute to the diagnosis and those that must be distinguished from pathologic lesions. Considering the novel classification proposed by the present study, physicians might be stimulated to reevaluate their opinions regarding artifacts, perhaps considering them helpful to evaluate certain conditions even if they cannot be fully corrected, as shown by this distinct approach to artifacts with specific findings concerning differential diagnosis of CNS conditions.
Keywords: artifacts; MRI; central nervous system